Analysis of a thermal cycle that surpass Carnot efficiency undergoing closed polytropic transformations (JOURNAL OF ADVANCES IN PHYSICS, 2019)
This research work deals with a feasible non-regenerative thermal cycle, composed by two pairs of closed polytropic-isochoric transformations implemented by means of a double acting reciprocating cylinder which differs basically from the conventional Carnot based thermal cycles in that:-it consists of a non condensing mode thermal cycle-all cycle involves only closed transformations, instead of the conventional open processes of the Carnot based thermal cycles,-in the active processes (polytropic path functions), as heat is being absorbed, mechanical work is simultaneously performed, avoiding the conventional quasi-adiabatic expansion or compression processes inherent to the Carnot based cycles and,-during the closed polytropic processes, mechanical work is also performed by means of the working fluid contraction due to heat releasing.An analysis of the proposed cycle is carried out for helium as working fluid and results are compared with those of a Carnot engine operating under the same ratio of temperatures. As a result of the cycle analysis, it follows that the ratio of top to the bottom cycle temperatures has very low dependence on the ideal thermal efficiency, but the specific work, and, furthermore, within the range of relative low operating temperatures, high thermal efficiency is achieved, surpassing the Carnot factor.